Complex traces: Examining morbidity and mortality among 19th Century migrants to South Australia using a Complex Adaptive Systems framework - Angela Gurr; Matthew Brook O’Donnell; Alan Henry Brook (PLoS ONE, 2025)
In multidisciplinary research interpreting interactions between diverse data sources requires a Complexity approach. A Complex Adaptive Systems (CAS) framework allows the relationships of multiple factors to be explored and may provide a more holistic and nuanced understanding. This study is innovative in explaining the potential benefits in a CAS approach to combining bioarchaeological and historical data when examining a rare archaeological skeletal sample of early migrants to South Australia (SA). Macroscopic, radiographic and micro-CT methods were used for the analysis of the skeletal remains of a group of 19th century migrants buried in an unmarked area of St Mary’s Anglican Church Cemetery. The relevant historical records explored were from British emigrant ships to SA (1836–1885 CE) and the Church burial records (1847–1885 CE). Evidence of poor oral and general health was present in the skeletal material. Dental developmental defects indicated health insults in early life. Pathological manifestations in bone were compatible with joint and infectious diseases, and metabolic deficiencies. Historical documents recorded that the voyages to SA were challenging, with some ships experiencing a high death rate. Diseases, e.g., measles and scarlet fever, and diarrhoea were frequently recorded as causes of death at sea for both non-adults and adults. In the Colony, burial records showed similar causes of death for non-adults, but for adults, accidents and tuberculosis were often reported. The CAS approach provided insights beyond those from analysis of the individual sources. It increased understanding of emergent, non-predicted outcomes that resulted from interactions between multiple factors, the impact of fluctuating economy, political instability and ideological pressures, on the health of migrants. The CAS framework is a valuable methodology for interpreting health patterns and can be further developed including for a range of historical and contemporary health contexts.